1981
DOI: 10.1159/000241398
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intrauterine Malnutrition on Brain Development: Alteration of Myelination

Abstract: As compared to other organs, in intrauterine growth retardation brain is less affected; however, forebrain weight and total lipids are reduced. Myelin quantity is reduced by 27, 17, 9 and 6% at 15, 18, 30 and 60 days after birth, respectively. Thus, intrauterine undernutrition followed by normal diet after birth affects myelination, a postnatal event. Prenatal growth retardation moderately but irreversibly impairs brain maturation, whereas the composition of myelin during maturation is close to normal (when de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…The CNP mRNA levels were close to normal in the heterozygous trembler mice which is in good agreement with the enzymatic assay for CNP previously performed in the mutant sciatic nerve [13,20]. In the homozygous trembler mice, where no myelin is assembled [17], the CNP mRNA quantities represent 50% of normal values.…”
Section: Discussionsupporting
confidence: 88%
“…The CNP mRNA levels were close to normal in the heterozygous trembler mice which is in good agreement with the enzymatic assay for CNP previously performed in the mutant sciatic nerve [13,20]. In the homozygous trembler mice, where no myelin is assembled [17], the CNP mRNA quantities represent 50% of normal values.…”
Section: Discussionsupporting
confidence: 88%
“…Data from the literature on animal models of IUGR have shown that the brain is the organ least affected by nutrient restriction (27,28). In humans, Larroche and Korn (29) described normal brain development in newborns with IUGR as far as weight, gross configuration, cytoarchitecture, and myelination are considered.…”
Section: Discussionmentioning
confidence: 99%
“…1971]. There is a slight reduction of cell num ber in human probably due to a decrease of cell multiplication [ Winick et al, 1970] and alteration of the relative quantities in brain cells in rat [Ross et al, 1970], In vitro, there is retardation in the outgrowth of IUGR culti vated rat cerebellum [Privat et al, 1972], We have previously shown [Bourre et al, 1981] that forebrain weight and total lipids are re duced in IUGR rat. Myelin quantity is re duced by 21, 17, 9 and 6% at 15, 18, 30 and 60 days after birth, respectively [Bourre el al., 1981], Thus, intrauterine undernutrition fol lowed by normal diet after birth affects myelination, a postnatal event.…”
Section: Introductionmentioning
confidence: 99%